Nausea and Vomiting Diagnosis and Treatment - Koch, Kenneth L.; Hasler, William L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume provides a comprehensive and state-of-the-art text for health care professionals who are interested in the diagnosis and treatment of nausea and vomiting. Because the majority of causes of nausea and vomiting arise from disorders of the gastrointestinal system, the text emphasizes the GI system by organ from esophagus to colon. It also reviews how disorders of the abdominal wall, the endocrine system, and autonomic and central nervous systems can contribute to nausea and vomiting syndromes that can be difficult to diagnose. Various treatment modalities are presented and organized in terms of drug treatments, electrical stimulation devices, and dietary therapy and nutritional support. Furthermore, the book is enhanced by chapters on the pathophysiology of nausea, the pathophysiology of vomiting, the physiological changes in the brain during nausea and vomiting, and the psychological underpinnings of nausea and vomiting. And because many children are afflicted with unexplained nausea and vomiting, a chapter devoted to pediatric patients is also included. Written by authorities in the field, Nausea and Vomiting: Diagnosis and Treatment is a valuable resource that will help practitioners and healthcare providers consider specific diagnoses in treating the noxious and burdensome symptoms of nausea and vomiting. .
Physiology of Nausea -- The Physiology of Vomiting -- Nausea and Vomiting Related to Esophagus and Stomach Diseases -- Nausea and Vomiting Related to Non-Esophageal and Gastric Diseases of the Gastrointestinal Tract -- Nausea and Vomiting Associated with Abdominal Wall Pain -- Nausea, Vomiting and Hormonal Disorders -- Nausea and Vomiting Related to Autonomic Nervous System Disorders -- Nausea and Vomiting Related to the Central Nervous System Diseases -- Pharmacological Causes and Treatments of Nausea and Vomiting -- Gastric Electrical Stimulation, Pyloroplasty, Gastrectomy and Acustimulation for the Treatment of Nausea and Vomiting In the Setting of Gastroparesis -- Nutritional Management for Patients with Nausea and Vomiting and Gastroparesis or Dumping Syndrome -- Complementary and Alternative Medicine for Nausea and Vomiting -- Vomiting and Nausea in the Pediatric Patient -- The Psychophysiology of Nausea -- Future Directions in Understanding Nausea and Vomiting. .
Keywords: Medicine; Gastroenterology; Medicine & Public Health; Gastroenterology